Assessment of Vaccination Coverage Among Measles Cases in Children Aged 10 Months to 5 Years at Civil Hospital Karachi - Bai, Naila; Parkash, Oam; Mustafa, Aiza; Mustafa , Anum; Khan , Sajeela; Ahmed, Naseem (International Journal of Endorsing Health Science Research, 2024)
Background: Measles remains a global health concern, particularly in developing countries, and despite improvements in global vaccination efforts, certain regions, including Pakistan, continue to report cases. This study aims to assess the frequency of vaccinated children among measles cases, shedding light on potential vaccine failure factors. Methodology: A comprehensive analysis was conducted on 139 children diagnosed with measles in an emergency department. The vaccination status of each child was determined through a thorough examination of their vaccination history and available vaccination cards. In cases where records were unavailable, relevant data were meticulously recorded on a standardized Performa. Results: Among the 139 children studied, 30.94% were found to have received vaccinations, and only 35.9% had completed the recommended two-dose schedule. The average age for receiving the first and second doses was 9.6±1.05 months and 15.67±0.82 months, respectively. Conclusion: The findings underscore that a substantial proportion of measles cases occurred in unvaccinated or partially vaccinated children, emphasizing the critical role of complete immunization. However, despite vaccination efforts, many children still contracted the disease, indicating the necessity for further in-depth research in this domain.